Disposal of plasma heme in normal man and patients with intravascular hemolysis - Sears, David A. (The Journal of Clinical Investigation, 1970)
The clearance of plasma protein-bound heme, its sites of removal, and the reutilization of hemeiron were studied by radioisotopic techniques in normal human subjects and in patients with intravascular hemolysis. In normal subjects, injected heme-59Fe was bound immediately by albumin and the β1-globulin, hemopexin. Its clearance from the plasma was descr bed by a single exponential equation, and the half-life in plasma was 7-8 hr. Removal was largely by the liver. Iron reutilization began promptly, and half the injected heme-iron was incorporated into circulating red cells within one cell life-span. In patients with intravascular hemolysis, hemopexin was depleted, and injected heme was bound solely to albumin. Plasma clearance was described by a double exponential equation of the form: y = Ae-k1t + Be-k2t. The half-lives of the two components averaged 3.9 and 22.2 hr, respectively. Removal was by the liver in at least some of the patients, and iron reutilization was variable, depending on the state of body iron stores. When hemopex'n was depleted in a normal subject by repeated heme injection, clearance mimicked that observed in the patients. Images